A Study on Teachers' Perceptions towards Cultural Arts Subject Using Wayang Kulit Purwa to Students of Junior High School in Solo Raya - Slamet Subiyantoro; Siti S Fadhilah (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2020)
This study revealed the perception of cultural arts teachers on the local Javanese wayang kulit purwa media to instilling students’ character values through learning art and culture at junior high school levels throughout the great Solo (Solo Raya) area. There is a previous assumption that wayang kulit purwa has only been performed at general public beyond formal school institutions such as junior high schools. Meanwhile, in instilling the values of character education, the teachers indicated through the subjects taught, the results showed that they were still found to be limited to formal media. This study reflects its own specific points, this is because the teaching aids used are the Purwa puppet media. This study was carried out by applying a survey to 69 cultural arts teachers who were selected purposively in all areas of Solo Raya covering 7 (seven) regencies / municipalities. The technique applied in collecting data is through questionnaires and interview techniques. To analyze the data, an interactive model is used which includes the initial steps of data collection, data reduction, data presentation and drawing conclusions. The results showed that most cultural arts teachers had positive and negative perceptions of wayang kulit purwa if it was used as a medium of learning and planting character education for students at junior high school level. However, most of the cultural arts teachers who have had a graduate education have positive perceptions. Because wayang kulit purwa reflects moral, socio-cultural values, character education as well as patriotism